Ang lihim ni Antonio - Altarejos, Joselito (Viva Video., 2011)
Adolescent curiosities and sexual explorations of a 15-year-old boy named Antonio who's just coming to terms with his sexuality. Through Antonio's mother and friends, we get an interesting look at what people in Manila think about homosexuality and gay people. Antonio's life takes a turn when his uncle comes to stay with him and his mother.